Advanced flight control Systems: integration of AI and adaptive control - Mahabub Sultan (PT Pustaka Intelektual Sutajaya, 2026)
This paper presents a comprehensive study on the implementation and simulation of advanced flight control systems for Unmanned Aerial Vehicles (UAVs). The work is divided into two primary domains: the practical application of the Pixhawk Pilot Support Package (PSP) within the MATLAB/Simulink environment and the theoretical construction of a six-degree-of-freedom (6-DOF) dynamic model for fixed-wing aircraft. By leveraging the PSP, we demonstrate the integration of hardware-in-the-loop (HIL) components, including sensor fusion via uORB and actuator control. Furthermore, a high-fidelity Python-based simulation is developed to validate the 6-DOF equations of motion and control law effectiveness. This research highlights the synergistic integration of established flight control methodologies with modern simulation tools, providing a robust framework for the development and testing of advanced UAV systems. The findings contribute to the understanding of complex flight dynamics and the practical application of AI and adaptive control principles in aerospace engineering.